Impact of deep brain stimulation on people with Parkinson's disease: A mixed methods feasibility study exploring lifespace and community outcomes. Issue 2 (December 2019) - Liddle, Jacki; Sundraraj, Amreetaa; Ireland, David; Bennett, Sally; Stillerova, Tereza; Silburn, Peter
Background: Deep brain stimulation is a surgical treatment for Parkinson's disease. Its impacts on motor symptoms are widely reported; however, little is known about the broader impact of deep brain stimulation on the community lives of people with Parkinson's disease. Lifespace is a measure of lived community mobility, providing an indication of community access and participation. Aims: This pilot study explored the feasibility of remotely monitoring the qualitative and quantitative community outcomes related to deep brain stimulation. Methods: A longitudinal mixed methods study with a convergent design was undertaken exploring the lifespace, quality of life, life satisfaction and lived experiences of people with Parkinson's disease before and after deep brain stimulation. Data were collected through questionnaires, semi-structured interviews and a smartphone-based application which collected geolocation data. Results: Quantitative and qualitative data from eight participants living with Parkinson's disease were analysed and integrated. At baseline, participants had a median age of 68 years and a median Hoehn and Yahr score of 2. Measuring a range of community-based outcomes indicated different change trajectories for individuals across outcomes. Key content areas were developed from the qualitative data: participation in occupations and travel and home. This study indicates the potential value of including geolocation data-based lifespace collection in metropolitan and regional areas. Conclusions: Monitoring lifespace in conjunction with subjective measures provides insights into the complex and individually varied experiences. Further research could explore the impacts of deep brain stimulation on occupations and community participation to gain a deeper understanding of the related needs and support clinical approaches.